If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8 + -2) + 5x = 18 Combine like terms: 8 + -2 = 6 3(6) + 5x = 18 Multiply 3 * 6 18 + 5x = 18 Add '-18' to each side of the equation. 18 + -18 + 5x = 18 + -18 Combine like terms: 18 + -18 = 0 0 + 5x = 18 + -18 5x = 18 + -18 Combine like terms: 18 + -18 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| -36/9/7(-23/4)= | | 2+3(x-8)+1=5x-2(x+9) | | 4=6r+7-7r | | 110+9x=15.50 | | 2x=34+8x | | 110+9x=14.50 | | 5x-2(x+6)+2=10-x | | 0.3(p-2)=5-0.6 | | 100+10.5x=16.5x | | 100+10.5x=16x | | 5m-3=3m-7 | | 3(x-16)-(x+10)=-22 | | 75+10.5x=15.50x | | -4(3y-8)+3(2y+10)= | | 0.6(x-8)=3.6 | | N×3/5=1 | | 14n+11=5(n+4) | | 5(x-3)-4(2x-1)=100 | | 6(x+1)-7x=-14 | | 3/8-n=2/24 | | 7(r-7)= | | 4y-z=0 | | x(5x-2)-19(5x-2)=0 | | 2(4n+8)+7n-2n=178 | | 5m+20=8m-16 | | 9(3+v)= | | 9h-2h+-18h=14 | | 2x+9y+5x-2=10 | | 6x-4z=0 | | 4x+3(x+1)=1 | | 5/2x=53 | | 2x^2-4x-y^2-24y-13=0 |